IDENTIFIKASI EKTOPARASIT PADA TIKUS DAN CECURUT DI DAERAH FOKUS PES DESA SUROTELENG KECAMATAN SELO KABUPATEN BOYOLALI (HASIL SURVEI BULAN AGUSTUS 2011) - Yusup Maulana; Diah Ika Rahma; Jarohman Raharjo; Anggun Paramita Djati (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2012)
Introduction: Plague is one of public health problem that can cause outbreak epidemic or that necessary guarded. Activity observed in humant and rodent activity in paste focus area should be done continuously to prevent outbreak. Rodent and human observation result in 2005 showed there were 11 patiens with a positive titer in the District of Selo. Examinations results in Rodent and it's flea still foud positive bacteria at serologist or bacteriology test, it's why Selo and Cepogo District need to be guarded. The aimed of this research were to count the trap success rats, identifying species of rats, identify diversity ectoparacites in mice , identify the species caught and count fleas General Flea Index on Rats, as plaque basic control efforts.Methods: A cross sectional study with collection of data using observation form and rat spot survey.Result and Discussion: Rat species found in Suroteleng Village, Selo Subdistrict, Boyolali District, were Rattus tanezumi (36.4%) and Rattus tiomanicus (27.3%) and Suncus murinus (36.4%). There were two species of ectoparacites were found namely Stivalius cognatus and Xenopsylla cheopis. General Flea Index as much 3.36. Number more than standart of General Flea Index it mean that potential to spread disease to humans.Conclusions and Recommendations: Rat control efforts eraound the settlement needs to be improved, together with active community participation.